Primerjalna analiza motiva deklice brez rok (ATU 706) (Филолошке студије, 2019)
Paper shows comparative analysis of folktales of handless maiden (ATU 706) type in correlation with Cinderella (AR 510 B) type. In the introduction are presented the previous variants (Straparola, Basile, Perrault, Grim, Gonzenbach) and three Slovenian variants e. G. Lord's wife, Handless maiden and Stepmother. The paper applies feminist approach by Marie Louise von Franz and Clarisse Pinkola Estes and sociological by Jack Zipes that researches this type as motif of incestuous and betrayed father. This motif is part of European culture from Greek, Bible, and medieval and new era. The research emphasises the differences between European and Slovenian variants and also between Slovenian variants.